2008
DOI: 10.1158/1055-9965.epi-07-2554
|View full text |Cite
|
Sign up to set email alerts
|

Does Breast Size Modify the Association between Mammographic Density and Breast Cancer Risk?

Abstract: Background: Both the absolute and the percent of mammographic density are strong and independent risk factors for breast cancer. Previously, we showed that the association between mammographic density and breast cancer risk tended to be weaker in African American than in White U.S. women. Because African American women have a larger breast size, we assessed whether the association between mammographic density and breast cancer was less apparent in large than in small breasts. Methods: We assessed mammographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
3
23
1
Order By: Relevance
“…Consistent with the trends and effects seen in our studies, the association of absolute dense area with BC risk was found to be decreased for larger breasts [50]. Investigators in two large case-control studies (634 cases:1880 controls [51] and 1424 cases:2660 controls [52]) and a prospective study of 111 cases of BC [53] all found statistically significant inverse associations of non-dense breast area with BC risk.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the trends and effects seen in our studies, the association of absolute dense area with BC risk was found to be decreased for larger breasts [50]. Investigators in two large case-control studies (634 cases:1880 controls [51] and 1424 cases:2660 controls [52]) and a prospective study of 111 cases of BC [53] all found statistically significant inverse associations of non-dense breast area with BC risk.…”
Section: Discussionsupporting
confidence: 88%
“…Prior findings published by Stuedal and colleagues [14] lend indirect to support to the notion that nondense mammographic area is inversely associated with breast cancer risk. Stuedal and colleagues examined if the association between mammographic density and breast cancer risk differs according to the size of the breasts.…”
Section: Discussionmentioning
confidence: 95%
“…Stuedal and colleagues examined if the association between mammographic density and breast cancer risk differs according to the size of the breasts. They used the total breast area on a mammogram as a proxy for breast size and found that the association between absolute dense area and breast cancer risk was significantly lower in larger breasts [14]. For percentage dense area, the results were similar, although weaker and nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Mammographic density may reflect cumulative exposure to endogenous estrogens, which may increase breast cancer risk through its mitogenic effects (40). Breast size has been reported to modify the association of dense area with breast cancer, with weaker associations found in larger breasts (48). Thus, the inverse associations of late adolescent BMI with breast density and cancer risk may be mediated by increased non-dense (fatty) area and adipocytes that support normal breast epithelial proliferation throughout puberty and inhibit later carcinogenesis (40).…”
Section: Discussionmentioning
confidence: 99%